The polar bear piper - David, Erica (David, Erica. Anna & Elsa, 2015)
"Even though Arendelle is a cold, snowy place, polar bears have always been a very rare sight -- until now. A family of polar bears has been spotted on the outskirts of town, and it has started to cause all kinds of mischief. Olaf loves the bears, but Elsa and Anna need to figure out why they have suddenly disppeared -- and how to lure them back to their Arctic home!" -- back cover.